Solubility Enhancement of Pioglitazone by Solid Dispersion Method - Bansal, Mayank; Vaghela, Bharat J.; Gupta, Rakesh Kumar; Garg, Nitin (Journal of Biomedical and Pharmaceutical Research, 2022)
The major challenge with conventional dosage forms of Pioglitazone is poor aqueous solubility. Through this study are to improve its aqueous solubility by preparing its solid dispersion by fusion method using various carriers that will improve its absorption and subsequent bioavailability. The solid dispersions of Pioglitazone were prepared using PEG-4000, PEG-6000 and PVP K30 as carrier, using fusion method. Solid dispersions of Pioglitazone were prepared using PEG-4000, PEG-6000 and PVP K30 as carrier, using fusion method and total 9 formulation (F1-F9) were prepared. Tablets were prepared (TF5) from the optimum formulation (F5). The prepared tablets (TF5) were subjected to evaluation for parameters like shape and size, weight variation, hardness, friability, disintegration time, drug content etc. The solid dispersion (F5) as well as the tablet (TF5) showed greater rate and extent of dissolution as compared to pure drug.Keywords: bioavailability, dissolution rate, PEG, PVP K30, solid dispersion, Pioglitazone